Immediate Psychosocial Impact on Healthcare Workers During COVID-19 Pandemic in China: A Systematic Review and Meta-Analysis - Dong, Fei; Liu, Hong-liang; Yang, Ming; Lu, Chun-li; Dai, Ning; Zhang, Ying; Robinson, Nicola; Liu, Jian-ping (Frontiers in Psychology, 2021)
Objectives: The corona virus disease-2019 (COVID-19) pandemic spread globally and we aimed to investigate the psychosocial impact on healthcare workers (HWs) in China during the pandemic. Methods: In this systematic review and meta-analysis, we searched seven electronic databases for cross-sectional studies on psychosocial impact on HWs in relation to COVID-19 from Jan 1, 2020 to Oct 7, 2020. We included primary studies involving Chinese HWs during the pandemic and data were extracted from the published articles. Our primary outcome was prevalence of anxiety, depression and stress disorders. We pooled prevalence value with their 95% confidence interval (CI) using random effect models and assessed study quality on the basis of 11-item checklist recommended by the Agency for Healthcare Research and Quality. The study protocol was registered in PROSPERO (CRD42020195843). Results: We identified 25 articles comprising a total of 30,841 completed questionnaires and 22 studies for meta-analysis. The prevalence of anxiety, depression and stress disorders was 34.4% (29.5%-39.4%), 31.1% (24.5%-37.7%), 29.1% (24.3%-33.8%) for HWs. The pooled prevalence of anxiety disorders for HWs from late January to early February was 46.4% (42.9%-49.9%), significantly higher than those in mid-term February(28.0%, 23.9%-32.1%) and after late February(27.6%, 16.0%-39.2%). The pooled prevalence of depression disorders for HWs from late January to early February was 46.5% (38.8%-54.2%), significantly higher than those in mid-term February(27.1%, 19.8%-34.5%) and after late February(32.9%, 16.2%-49.5%). HWs working in Hubei Province had a higher prevalence of anxiety (37.9% vs 30.8%) and a lower prevalence depression (27.5% vs 34.7%) than those working in other regions. Nurses had a higher prevalence of anxiety (44.1% vs 29.0%) and depression (34.1% vs 29.2%) than other HWs. Conclusions: About one third of HWs in China suffered anxiety, depression and stress at the early epidemic of COVID-19, HWs in Hubei Province, especially nurses had higher prevalence of psychological disorders. During the pandemic, negative psychological state may persist in a proportion of Chinese HWs, fluctuating with the control of the pandemic. The long-term impact should continue to be observed. Attention should be paid to HWs for their psychological impact due to the pandemic.